The Influence of Academic Supervision and Principal Leadership on the Professionalism teachers - Akmal, Ikhwani; Ahyani, Nur; Wardiah, Dessy (Jurnal Pendidikan Tambusai, 2021)
This research aims to identify and describe: 1). academic supervision of teacher professionalism; 2) the influence of the principal's leadership on teacher professionalism, 3) the influence of academic supervision and the leadership of the principal on teacher professionalism. This research uses the descriptive quantitative method. The population in this study were 47 teachers at SMP Negeri Sinar Peninjauan District. The data collection techniques used were questionnaires and documentation. Data were analyzed using simple linear regression formulas and multiple linear regression. The results showed that: 1) There was a significant effect of academic supervision on professionalism; 2) There is a significant influence of principal leadership on teacher professionalism; 3) There is a significant effect of academic supervision and principal leadership on teacher professionalism. The magnitude of the influence of academic supervision and principal leadership together on teacher professionalism is 73.2% and the remaining 26.9% is influenced by other factors.